Measuring the impact of an acute visiting scheme on emergency department attendances - a pre-post cohort design - Axel Kaehne; Paula Keating (BMC, 2021)
Abstract Background Emergency department (ED) attendances are contributing to rising costs of the National Health Service (NHS) in England. Critically assessing the impact of new services to reduce emergency department use can be difficult as new services may create additional access points, unlocking latent demand. The study evaluated an Acute Visiting Scheme (AVS) in a primary care context. We asked if AVS reduces overall ED demand and whether or not it changed utilisation patterns for frequent attenders. Method The study used a pre post single cohort design. The impact of AVS on all-cause ED attendances was hypothesised as a substitution effect, where AVS duty doctor visits would replace emergency department visits. Primary outcome was frequency of ED attendances. End points were reduction of frequency of service use and increase of intervals between attendances by frequent attenders. Results ED attendances for AVS users rose by 47.6%. If AVS use was included, there was a more than fourfold increase of total service utilisation, amounting to 438.3%. It shows that AVS unlocked significant latent demand. However, there was some reduction in the frequency of ED attendances for some patients and an increase in time intervals between ED attendances for others. Conclusion The study demonstrates that careful analysis of patient utilisation can detect a differential impact of AVS on the use of ED. As the new service created additional access points for patients and hence introduces an element of choice, the new service is likely to unlock latent demand. This study illustrates that AVS may be most useful if targeted at specific patient groups who are most likely to benefit from the new service.